Mechanical properties, and in vitro biocompatibility assessment of biomimetic dual layered keratin/ hydroxyapatite scaffolds - Feroz, Sandleen; Muhammad, Nawshad; Ullah, Riaz; Nishan, Umar; Cathro, Peter; Dias, George (Frontiers in Bioengineering and Biotechnology, 2023)
A novel biomimetic dual layered keratin/hydroxyapatite (keratin/HA) scaffold was designed using iterative freeze-drying technique. The prepared scaffolds were studied using several analytical techniques to better understand the biological, structural, and mechanical properties. The developed multilayered, interconnected, porous keratin scaffold with different hydroxyapatite (HA) content in the outer and inner layer, mimics the inherent gradient structure of alveolar bone. SEM studies showed an interconnected porous architecture of the prepared scaffolds with seamless integration between the upper and lower layers. The incorporation of HA improved the mechanical properties keratin/HA scaffolds. The keratin/HA scaffolds exhibited superior mechanical properties in terms of Young's modulus and compressive strength in comparison to pure keratin scaffolds. The biocompatibility studies suggested that both keratin and keratin/HA scaffolds were cyto-compatible, in terms of cell proliferation. Furthermore, it showed that both the tested materials can served as an ideal substrate for the differentiation of Saos-2 cells, leading to mineralization of the extracellular matrix. In summary, ionic liquid based green technique was employed for keratin extraction to fabricate keratin/HA scaffolds and our detailed in vitro investigations suggest the great potential for these composite scaffolds for bone tissue engineering in future.